Role of a Teacher in Innovative Education and Development of Institute - Shankar, Girija (IJRDO-Journal of Applied Science, 2015)
Innovation is defined as “the process of making changes to something established by introducing something new.” Over the years there have been many changes in the way education is designed and delivered in parts of the world. How can innovation and technology offset the barriers of access and mobility that has been a deterrent to education in many parts of the developing world?